Photoinduced reactivity in a Dispiro-1,2,4-trioxolane: Adamantane ring expansion and first direct observation of the long-lived triplet diradical intermediates - M Brás, Elisa (2021)
Dispiro-1,2,4-trioxolane, 1, an ozonide with efficient and broad antiparasitic activity, was synthesized and investigated using matrix isolation FTIR and EPR spectroscopies together with both B3LYP/6-311++G(3df, 3dp) and M06- 2X/6-311++G-(3df,3dp) theoretical methods. Irradiations (lambda >= 290 nm) of the matrix isolated 1 (Ar or N-2) afforded exclusively 4-oxahomoadamantan-5-one, 4, and 1,4-cyclohexanedione, 5. These results suggested that the reaction proceeded via a dioxygen-centered diradical intermediate, formed upon homolytic cleavage of the labile peroxide bond, which regioselectively isomerized to form the more stable (secondary carbon-centered)/oxygen-centered diradical. In situ EPR measurements during the photolysis of 1 deposited in a MeTHF-matrix led to the detection of signals corresponding to two triplet species, one of which was short-lived while the other proved to be persistent at 10 K. These observations strongly support the proposed mechanism for the photogeneration of 4 and 5, which involves intramolecular rearrangement of the intermediate diradical species 2 to afford the triplet diradical 3.